Thrombolysis in Stroke within 30 Minutes: Results of the Acute Brain Care Intervention Study - Zinkstok, Sanne M. (PLoS One, 2016)
BACKGROUND AND PURPOSE: Time is brain: benefits of intravenous thrombolysis (IVT) in ischemic stroke last for 4.5 hours but rapidly decrease as time progresses following symptom onset. The goal of the Acute Brain Care (ABC) intervention study was to reduce the door-to-needle time (DNT) to ≤30 minutes by optimizing in-hospital stroke treatment. METHODS: We performed a single-centre before (pre-intervention period: 2000–2005) versus after (post-intervention period: 2006–2012) comparison in a cohort of consecutive patients treated with IVT. The intervention consisted of the implementation of a multidisciplinary stroke protocol combining simple strategies to reduce the DNT. Primary endpoint was the DNT, presented as proportion ≤30 minutes and median time. Secondary clinical endpoints were symptomatic intracranial hemorrhage (SICH), and favourable outcome defined as a modified Rankin scale (mRs) score of 0–2 at 3 months. Endpoints were additionally adjusted for baseline imbalances between the groups. RESULTS: In the pre-intervention period, none (0.0%) of the 100 patients (mean age 63.8 years, median National Institutes of Health Stroke Scale [NIHSS] score 14) treated with IVT had a DNT ≤30 minutes compared to 234 (62.7%) of the 373 patients (mean age 66.7 years, median NIHSS score 10) in the post-intervention period (p<0.001). The median DNT decreased from 75 (IQR 60–105) to 28 minutes (IQR 20–37, p<0.001). SICH rate remained stable (3.0% versus 4.4%, OR 1.50, 95% CI 0.43─5.25; adjusted OR 5.47, 95% CI 0.69–42.12). The proportion of patients with a favourable outcome increased (38.9% versus 52.3%, OR 1.72, 95% CI 1.09–2.73) but lost statistical significance after adjustment (adjusted OR 1.46, 95% CI 0.82–2.61). CONCLUSIONS: Important and sustained reduction of the DNT to 30 minutes or less can be safely achieved by optimizing in-hospital stroke treatment. With its simple strategies, the ABC-protocol is a pragmatic framework for increasing the therapeutic yield in time-dependent stroke treatment.